GLOPOLI: INOVASI BOARD GAME 4 DIMENSI PERJALANAN KELILING DUNIA BERBENTUK GLOBE SEBAGAI UPAYA MENINGKATKAN WAWASAN - Rosyidah, Fifi Alfiana; Ismail, Andhanu Surya; Dewi, Silvia Roshita; Ramadhani, M. Lutfi; Lihawa, M. Faizal (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Global knowledge can make children have a big imagination about world. And they can have a dream that bigger and higher. But, there isnât a tools that can help children learn more about global knowledge. Glopoli, the innovation of board game 4 dimension travel around the world to improve global knowledge for children is the solution in this paper. With play Glopoli, child can learn about so many countries in the world, the location of the state, the characteristic of state and after playing they dare to dream travel around the world. And then, they make changes from the smallest thing to realize their dream.